MODEL KOMUNIKASI DAN PEMBENTUKAN KONSEP DIRI (Studi Deskriptif Kualitatif mengenai Model Komunikasi Pembimbing dalam Proses Pembentukan Konsep Diri pada Klien di Balai Rehabilitasi Sosial âKARTINIâ Tawangmangu) - Jati, Tawangsari Anindya; Hastasari, Chatia; Ruthnia, Firdastin (KOMUNITAS, 2013)
The phenomenon of children on the street is increasingly widespread. This due to the fact that existence is very easy to find particulary in the city center or street even almost all them are disturbing the society, the naughty child and the children on the street tend to live freely with singing on the street and so on. Therefore it needs to establish aÂ positiveÂ self conceptÂ for naughty child and childrenÂ onÂ the street. The objective of the research is to determine the comunication model and to classify effective communication model used by conselors in the process of self concept establishment in the client. This research belongs to qualitative descriptive study, data collection techniques usedÂ observationÂ andÂ interview.Â TheÂ resultsÂ ofÂ this researchÂ isÂ theÂ processÂ of establishing aÂ positive self-conceptÂ onÂ theÂ clientÂ inÂ socialÂ rehabilitation centers âKARTINIâ Tawangmangu through three stages of social rehabilitation services consists of some guidance such as the guidance of physical, mental, social skill andÂ character.Â TheÂ guidanceÂ usesÂ twoÂ communicationÂ models.Â TheÂ first communication model effective to estabilish a positive self concept in client with the problems such as ropping out of school, hanging out and so on. Mean while the second communication model effective to clientwhich specific problems such as broken home, drunk, sing on the street and so on.